Guía metodológica para el análisis de la gestión de embalses. Caso de estudio embalse la copa. (2019)
This document was developed as a contribution to manage the problematic related to availability and control of water on regulated basins, during wet or dry hydrologic periods. The main purpose of this document is to develop a methodology to study and manage reservoirs through quantitative methods. A suggested process to construct a reservoir simulation model employing the HEC-ResSim software is analyzed through a case study. The process will allow to improve the operation for a given reservoir (whether it is projected or existing) with the definition of the optimal reservoir guide curve. To achieve this objective secondary processes are carried out, some of those are: continuous hydrological modeling (employing HEC-HMS with SMA as the loss method) which, after its calibration, will provide with annual time series of daily average discharge; the construction of a 2D-hydrodynamic model (using HEC-RAS 2D) which will allow to know the benefits of reservoir regulation when modeling the current and the optimal operation situations; and all the complementary processes necessary to build those models. La Copa reservoir is selected as the case study, it is located between the cities of Tunja and Paipa, in the department of Boyaca, Colombia. La Copa reservoir’s release form the Tuta river. After being discharged from the reservoir, the Tuta river confluences with the Jordán river to become the Chicamocha river, which supplies water to an irrigation district. It is important to mention the Jordán river is also regulated by La Playa reservoir; however, the study of this reservoir is out of the scope of this research. Determination of the guide curve is a key step in order to achieve a reservoir’s optimal operation, this is because both field reservoir operation and reservoir simulation (using the software HEC-ResSim) are function of the reservoir guide curve. In this study, several methodologies to determine a system’s guide curve are proposed, those curves are modeled and their results are compared. This is done without disregarding alternative methodologies that can give a better guide curve. For the case study, numerous guide curves were found using different methodologies; however just four of them were selected to make the comparison. The curves were tested through the analysis of the reservoir simulation results; a quantification of the excess and deficit volumes were conducted based on the simulated releases. Finally, a guide curve was selected for La Copa reservoir being the one which minimizes the excess and deficit water volume in both dry and wet hydrological conditions.